How Self-Objectification Impacts Physical Activity Among Adolescent Girls in Costa Rica - Monge Rojas, Rafael (2017)
Background: In Latin America, more than 80% of adolescent girls are physically inactive. Inactivity may be reinforced by female stereotypes and objectification in the Latin American sociocultural context. Methods: We examined the influence of objectification on the adoption of an active lifestyle among 192 adolescents (14 and 17 years old) from urban and rural areas in Costa Rica. Analyses of 48 focus-groups sessions were grounded in Objectification Theory. Results: Vigorous exercises were gender-typed as masculine while girls had to maintain an aesthetic appearance at all times. Adolescents described how girls were anxious around the prospect of being shamed and sexually objectified during exercises. This contributed to a decrease in girls’ desire to engage in physical activities. Among males, there is also a budding tolerance of female participation in vigorous sports, as long as girls maintained a feminine stereotype outside their participation. Conclusion: Self-objectification influenced Costa Rican adolescent girls’ decisions to participate in physical activities. Interventions may include: procuring safe environments for physical activity where girls are protected from fear of ridicule and objectification; sensitizing boys about girl objectification and fostering the adoption of a modern positive masculine and female identities to encourage girls’ participation in sports.